Serum Immunoglobulin Concentrations in Racing Endurance Horses. (June 2014) - McKenzie, E; Esser, M; Payton, E
Abstract : Introduction: Serum immunoglobulin fractions were evaluated in horses participating in multi‐day endurance exercise. Methods: Serum IgGa, IgGb, IgG(T), IgA, and IgM were measured using horse‐specific ELISA kits in 44 trained horses prior to racing, after each day of racing 50 miles per day and in 15 untrained matched control horses. Data were analyzed via repeated measures ANOVA (P<0.05). Results: 44, 18 and 9 horses completed one, two and three days of racing, respectively. Serum IgA before racing (1.97 ± 0.14 mg/dL) was similar to controls (1.48 ± 0.19) and after one, two or three days of racing (1.98 ± 0.13, 1.80 ± 0.15 and 1.76 ± 0.26). Serum IgM before racing (1.02 ± 0.05 mg/dL) was similar to controls (1.08 ± 0.12) and after one, two or three days of racing (1.03 ± 0.06, 0.91 ± 0.08 and 0.89 ± 0.11). Serum IgG(T) before racing (6.10 ± 0.41 mg/dL) was similar to controls (6.29 ± 0.58) and after racing one, two or three days (6.23 ± 0.45, 6.62 ± 0.63, and 6.65 ± 1.34). Serum IgGa was 2.41 ± 0.10 mg/dL before racing, and was similar to controls (2.45 ± 0.22) and each day of racing (2.58 ± 0.14, 2.39 ± 0.20, and 2.61 ± 0.22, on days one, two and three of racing). Resting serum IgGb concentration was significantly lower in control (5.71 ± 0.54 mg/dL) than trained horses (7.65 ± 0.41). Conclusions: Serum IgGb is higher in trained endurance horses, perhaps reflecting immune stimulation related to disease exposure or more frequent vaccination. Ethical Animal Research: All procedures were approved by the Oregon State University Institutional Animal Care and Use Committee. Owner informed consent was obtained for all horses in the study.Sources of funding:  Department of Biomedical Sciences at Oregon State University.Competing interests:  none.